2020
DOI: 10.21037/tcr.2020.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CYB5D2 expression is associated with epithelial-mesenchymal transition and survival rates in patients with cervical cancer

Abstract: Background: CYB5D2 is a member of the membrane-associated progesterone receptors (MAPRs) family and plays essential roles in regulating nerve development. CYB5D2 is associated with tumor suppression in breast cancer. Despite the potential implication of CYB5D2 in cancer progression, its level and clinical significance in cervical cancer tissues has not been investigated yet. Via this study, we aimed to investigate the possible role played by CYB5D2 in epithelial-mesenchymal transition (EMT) in cervical cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Other studies have also shown that CYB5D2 helps prevent the formation of cervical cancer, and up-regulating the expression of this gene can prevent the malignant progression of human cervical cancer HeLa cells (12). It has been demonstrated that individuals with cervical cancer who express high levels of CYB5D2 mRNA have a better prognosis for their condition in the study of Li D et al, and this gene mainly reduced epithelial-mesenchymal transition (EMT) via decreasing the production of E-cadherin (13). Currently, the mechanistic role of CYB5D2 in HCC is not fully understood, necessitating further investigation to elucidate its potential function and impact on HCC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that CYB5D2 helps prevent the formation of cervical cancer, and up-regulating the expression of this gene can prevent the malignant progression of human cervical cancer HeLa cells (12). It has been demonstrated that individuals with cervical cancer who express high levels of CYB5D2 mRNA have a better prognosis for their condition in the study of Li D et al, and this gene mainly reduced epithelial-mesenchymal transition (EMT) via decreasing the production of E-cadherin (13). Currently, the mechanistic role of CYB5D2 in HCC is not fully understood, necessitating further investigation to elucidate its potential function and impact on HCC progression.…”
Section: Introductionmentioning
confidence: 99%